Molecular and biochemical characterization of a new thermostable bacterial laccase from Meiothermus ruber DSM 1279. Issue 5 (6th January 2016) - Kalyani, D. C.; Munk, L.; Mikkelsen, J. D.; Meyer, A. S.
Abstract : A new bacterial laccase gene ( mrlac ) from Meiothermus ruber DSM 1279 was successfully overexpressed to produce a laccase (Mrlac) in soluble form in Escherichia coli during simultaneous overexpression of a chaperone protein (GroEL/ES). Abstract : A new laccase gene ( mrlac ) from Meiothermus ruber DSM 1279 was successfully overexpressed to produce a laccase (Mrlac) in soluble form in Escherichia coli during simultaneous overexpression of a chaperone protein (GroEL/ES). Without the GroEL/ES protein, the Mrlac overexpressed in E. coli constituted a huge amount of the total cellular protein, but the enzyme was localized in the insoluble fraction with no activity in the soluble fraction. Co-expression of the Mrlac with the E. coli GroEL/ES drastically improved proper folding and expression of active Mrlac in the soluble fraction. Spectroscopic analysis of the purified enzyme by UV/visible and electron paramagnetic resonance spectroscopy confirmed that the Mrlac was a multicopper oxidase. The Mrlac had a molecular weight of ∼50 kDa and exhibited activity towards the canonical laccase substrates 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), syringaldazine (SGZ), and 2, 6-dimethoxyphenol (2, 6-DMP). Kinetic constants K m and k cat were 27.3 μM and 325 min −1 on ABTS, 4.2 μM and 106 min −1 on SGZ, and 3.01 μM and 115 min −1 on 2, 6-DMP, respectively. Maximal enzyme activity was achieved at 70 °C with ABTS as substrate. In addition, Mrlac exhibited a half-life for deactivation at 70 °C and 75 °C of about 120 min and 67 min, respectively, indicating that the Mrlac is intrinsically thermostable. Finally, Mrlac was efficient in catalyzing the removal of 2, 4-dichlorophene (DCP) in aqueous solution, a trait which makes the enzyme potentially useful for environmentally friendly applications.